A Taxonomy of Initiatives at Work in the Sharing Economy. Issue 3 (August 2020) - Fernandes, Bruno; Chimenti, Paula; Nogueira, Roberto
It is crucial to classify SE initiatives to better understand such a multifaceted phenomenon. However, previous attempts to classify SE initiatives seem not to contemplate the full SE complexity. Therefore, this study proposes a new classification using a broad taxonomic approach. It started by systematically selecting a set of initiatives. Then, an intensive search on secondary data about the initiatives selected was conducted in order to identify relevant attributes. Next, the attributes identified were successively aggregated resulting in four attribute groups. In the end, each initiative was analysed from the perspective of each attribute group, resulting in five SE categories: commodity intermediary, wealth redistributor, unique-service intermediary, skill redistributor, and decentralized commodity intermediary. Findings suggest that generalizations from studies focused on specific initiatives might be problematic, entrepreneurs should consider the characteristics of different SE categories to design appropriate platforms, and policymakers should avoid regulating all SE initiatives in a homogeneous manner.